Release of Transforming Growth Factor Beta 1 from Human Tooth Dentin after Application of Either ProRoot MTA or Biodentine as a Coronal Barrier - Kunlada Wattanapakkavong (2019)
© 2019 American Association of Endodontists Introduction: Various factors may influence intracanal calcification in teeth treated with regenerative endodontic procedures. Bioactive materials, including ProRoot MTA (MTA; Dentsply Tulsa Dental Specialties, Memphis, TN)and Biodentine (BD; Septodont, Saint-Maur-des-Fossés, France), have been widely used as a coronal barrier in the final step of regenerative endodontic procedures. The purposes of this study were to evaluate the effect of either MTA or BD after application as a coronal barrier on transforming growth factor beta 1 (TGF-β1)release from root canal dentin and to observe the impact of these materials on human apical papilla cell (APC)mineralization. Methods: Either MTA or BD was applied in enlarged root canals of human root segments. After storing for 14 days in phosphate-buffered saline, TGF-β1 release was evaluated using an enzyme-linked immunosorbent assay. To investigate the effect of the materials on APC mineralization, APCs were grown in the presence of either the materials alone or material-filled root segments. Cell mineralization was quantified after 14 and 21 days using alizarin red S staining. Calcium deposits were quantitatively analyzed. Statistical analysis was performed using the Kruskal-Wallis and Mann-Whitney U tests with the significance level at.05. Results: The greatest amount of TGF-β1 release was observed in the root segments treated with BD. BD, used either alone or as a coronal barrier, promoted greater APC mineralization than did MTA on both days 14 and 21. Interestingly, when BD was applied as a coronal barrier, the mineralization effect was significantly reduced compared with the use of the materials alone (P <.05). Conclusions: When used as a coronal barrier, BD promoted the release of TGF-β1 from the root canal dentin. A higher mineralization effect was observed with BD than with MTA.